Kontribusi Social Support terhadap Problematic Internet Use pada Mahasiswa Universitas Negeri Padang - Rendra, Rashad Yazid; Mardianto, Mardianto (AHKAM, 2024)
The development of information and communication technology, particularly the internet, has significantly benefited Indonesian society, with internet users reaching 95% by 2024. Although the internet facilitates communication and access to information, excessive use can lead to mental health issues, especially among students, with 15% experiencing problematic internet use. Students often rely on the internet for social interaction and emotional management, which can increase the risk of addiction. This study aims to investigate the contribution of social support to problematic internet use among students at Universitas Negeri Padang. The research adopts a quantitative approach with statistical analysis. The population measured in this study consists of students at Universitas Negeri Padang. The sample was taken using a proportionate stratified random sampling technique, appropriate for populations with non-homogeneous and stratified members. A total of 395 students participated in the study. The instruments used were the GPIUS2 scale and the MSPSS scale, developed using the Likert model. The data obtained were analyzed using multiple regression analysis. The results show a coefficient of determination (R²) of 0.220, indicating that the social support variable contributes 22% to the problematic internet use variable.